Ships passing in the night? Opportunities to integrate the African Peer Review Mechanism: early warning findings within the African Union Peace and Security Architecture - Crause, Katarina (University of Pretoria, 2010)
A dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Katarina Crause, Institute for Human Rights, Abo Akademi University, Finland.